Identifying Professional Football Crowd Crisis Management Solutions: The Best-Worst Method - Nasrin Biglari; Seyed Reza Hosseini Nia; Hadi Bagheri; William Coombs (Shahid Bahonar University of Kerman, 2023)
Spectators are the main element of football. Football, as a popular sport, has the capacity for the intimate involvement and intense emotional experiences of the spectators. But the large presence of spectators in one place increases the probability of critical situations. Therefore, the purpose of this study is to identify crowd crisis management (CCM) solutions in professional football and to select the best solutions in terms of functional priority with mix-method. In the qualitative part, the approach based on thematic analysis was used to identify the crowd crisis management solutions and in the quantitative part, the best-worst method (BWM) was used to determine the importance and weight of the identified factors. A semi-structured interviews with 21 experts and the implementation of the best-worst method, demonstrated that among the five categories of solutions related to CCM inside the stadium, control, and guide of spectators as the most important, and emergency medical services as the least important of solutions. Also, among the solutions for managing the crowd crisis outside the stadium, the staff training of the stadium is illustrated to be the most important and financial discipline the least important solution effective for controlling the crowd crisis. Therefore, it is suggested that organizers of the matches focus on solutions that lead to the accurate implementation of the roles and tasks of the groups involved in holding the match and the development of programs, policies and effective security measures to control the spectators.